Total Drift: Theses on Urban Space-Times - Bueso, José Manuel (Re-visiones, 2024)
The coordinates of Global “North” and “South” lose their meaning under conditions of full dislocation of geopolitical tectonic plates. In Bagdad, París, Río, New Orleans, North and South coexist in the same territories. Cities and even whole nations may shift in the Earth’s crust from one day to the next. Detroit, Greece and Spain used to be in the “North” and are now in the “South”. Shifts and cross-hatching are not limited to space, but also occur along temporal planes -unsuspected geometries link past, present and future forms of dispossession and resistance. In fact, in the rhizomatic spacetime of our synchrony-city the past is never dead, it’s not even past; and the future is always already here, only unevenly distributed. As we become Blacks of Different Colours, in a whole neoliberal constellation of new, unevenly disempowered subjectivities of multiple kinds, our hope is symbolised precisely by the Black Jacobins who overcame Homo Sacer’s vulnerability and revolted in Haiti.